Student Pastor Models: The Incarnation of the Kenosis - Josette, Ramarolahy Patricia; Baholy, Robijaona Rahelivololoniaina (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2025)
When we talk about the Church, we usually think about the Pastors. Therefore, in order for our country to develop, the Church must recognize the importance of pastoral formation to ensure a relevant and effective proclamation of the Gospel. The present situation, however, indicates that individuals attach little importance to pastoral training. As a result, even pastors don't express much interest in considering the pastoral training center. The behavior and attitude of pastors toward their ministry have also changed. His behavior no longer meets the requirements of the Holy Scriptures. Today's pastors are becoming more materialistic. The spiritual side is no longer valued. It is important to write this article to make people aware that humility is one of the qualities needed in pastors. It sets an example for others to adopt a humble lifestyle. The humility of Jesus Christ is truly embodied in Him. In this article, we want to restore the value of theological education in the church and encourage a change of attitude and behavior in future pastors. That's why they need to be pastors who are determined to live humbly in order to serve as an example to others and to succeed in their mission. Therefore, the expected outcome of this article is to encourage pastors to imitate Jesus and to make Jesus a good example of behavior to follow. And also, to lead them to become witnesses of Jesus Christ and to live in true faith in the fear of God. However, what Pastors need to be aware of is that even if this teaching is given, it will not be fruitful if they are not spiritually mature. And the changes in them will not be achieved unless they have the conviction that they are truly people called by God to be Pastors.